DESAIN PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBANTU VIDEO INTERAKTIF PADA MATERI SIKLUS AIR DI KELAS V SD - Rani Fitri Nurhasanah; Akhmad Nugraha; Agnestasia Ramadhani Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning media is an important alternative to use in learning, especially in elementary schools. This interactive video media is used as a tool for teaching innovation in learning, especially in the water cycle material, in order to increase students' enthusiasm for learning and motivate students in learning to be more interactive. It is important to develop discussions regarding interactive video media in the world of teaching, so that educators can increase innovations in developing media used in learning activities. This pattern of design and development of interactive video media needs to be implemented well so that educators can review the development, effectiveness and efficiency of learning activities. Therefore, learning about the water cycle in learning can run well.